Genome sequencing of a virulent avian Pasteurella multocida strain GX-Pm reveals the candidate genes involved in the pathogenesis. (April 2016) - Yu, Chengjie; Sizhu, Suolang; Luo, Qingping; Xu, Xuewen; Fu, Lei; Zhang, Anding
Abstract: Pasteurella multocida ( P. multocida ) was first shown to be the causative agent of fowl cholera by Louis Pasteur in 1881. First genomic study was performed on an avirulent avian strain Pm70, and until 2013, two genomes of virulent avian strains X73 and P1059 were sequenced. Comparative genome study supplied important information for further study on the pathogenesis of fowl cholera. In the previous study, a capsular serotype A strain GX-Pm was isolated from the liver of a chicken, which died during an outbreak of fowl cholera in 2011. The strain showed multiple drug resistance and was highly virulent to chickens. Therefore, the present study performed the genome sequencing and a comparative genomic analysis to reveal the candidate genes involved in virulence of P. multocida . Sequenced draft genome sequence of GX-Pm was 2, 292, 886 bp, contained 2941 protein-coding genes, 5 genomic islands, 4 IS elements and 2 prophage regions. Notability, all the predicted drug-resistance genes were included in predicted genomic islands. A comparative genome study on virulent avian strains P1059, X73 and GX-Pm with the avirulent avian strain Pm 70 indicated that 475 unique genes were only identified in either of virulent strains but absent in the avirulent strain. Among these genes, 20 genes were contained within genomes of all three virulent strains, including a few of putative virulence genes. Further characterization of the pathogenic functions of these genes would benefit the understanding of pathogenesis of fowl cholera. Highlights: Genome sequencing of a virulent avian Pasteurella multocida strain GX-Pm 475 unique genes were only identified in either of three virulent strains. 20 genes were contained within genomes of all sequenced virulent strains.